Safety of a Novel Listeria monocytogenes-Based Vaccine Vector Expressing NcSAG1 (Neospora caninum Surface Antigen 1) - Pownall, William Robert; Imhof, Dennis; Trigo, Nerea Fernandez; Ganal-Vonarburg, Stephanie C.; Plattet, Philippe; Monney, Camille; Forterre, Franck; Hemphill, Andrew; Oevermann, Anna (Frontiers in Cellular and Infection Microbiology, 2021)
Listeria monocytogenes (LM) has been proposed as vaccine vector in various cancers and infectious diseases since LM induces a strong immune response. In this study, we developed a novel and safe LM-based vaccine vector platform, by engineering a triple attenuated mutant (Lm3Dx) (∆actA, ∆inlA, ∆inlB) of the wild-type LM strain JF5203 (CC 1, phylogenetic lineage I). We demonstrated the strong attenuation of Lm3Dx while maintaining its capacity to selectively infect antigen-presenting cells (APCs) in vitro. Furthermore, as proof of concept, we introduced the immunodominant Neospora caninum (Nc) surface antigen NcSAG1 into Lm3Dx. The NcSAG1 protein was expressed by Lm3Dx_SAG1 during cellular infection. To demonstrate safety of Lm3Dx_SAG1 in vivo, we vaccinated BALB/C mice by intramuscular injection. Following vaccination, mice did not suffer any adverse effects and only sporadically shed bacteria at very low levels in the feces (<100 CFU/g). Additionally, bacterial load in internal organs was very low to absent at day 1.5 and 4 following the 1st vaccination and at 2 and 4 weeks after the second boost, independently of the physiological status of the mice. Additionally, vaccination of mice prior and during pregnancy did not interfere with pregnancy outcome. However, Lm3Dx_SAG1 was shed into the milk when inoculated during lactation, although it did not cause any clinical adverse effects in either dams or pups. Also, we have indications that the vector persists more days in the injected muscle of lactating mice. Therefore, impact of physiological status on vector dynamics in the host and mechanisms of milk shedding requires further investigation. In conclusion, we provide strong evidence that Lm3Dx is a safe vaccine vector in non-lactating animals. Additionally, we provide first indications that mice vaccinated with Lm3Dx_SAG1 develop a strong and Th1-biased immune response against the Lm3Dx-expressed neospora antigen. These results encourage to further investigate the efficiency of Lm3Dx_SAG1 to prevent and treat clinical neosporosis.